Women and disasters in South Asia: survival, security and development - Racioppi, Linda; Rajagopalan, Swarna, 1964- (London : New York : Routledge, Taylor & Francis Group, 2016)
South Asia is one of the most vulnerable areas of an increasingly disaster-impacted world, with cyclones, earthquakes, floods and droughts causing several casualties and disrupting lives and livelihoods every year. Yet, the impacts of disasters are not equally distributed across the peoples of the region. Women and men experience disaster differently, and their needs in the aftermath of disaster often differ. Bringing together perspectives from academics, emergency responses and development practitioners, the volume investigates to what extent and in what ways gender affects the course of post-disaster reconstruction. Conversely, it also explores in what ways gender politics may be altered by disaster and post-disaster reconstruction. The study includes: a comprehensive overview of key issues facing women and men, as gendered beings, in reconstruction and development; a targeted observation of specific South Asian disaster contexts; and a sustained discussion of case studies and their implications and lessons . This book will interest scholars and researchers of disaster management, rehabilitation studies, gender, environment, ecology, and sociology.
Gender differential impacts of the 2004 tsunami / Chaman Pincha -- The interplay of women, work and disasters: missing women's views / Mihir Bhatt -- Livelihoods reexamined: the distribution of fisheries-sector aid and its impact on women's livelihoods in post-tsunami Tamil Nadu, India / Julia Novak Colwell -- Experiences of women with super cyclone in coastal Odisha / Mamata Swain, Mrutunjay Swain and Ranju H. Sahoo -- Gender play in economic redevelopment in post-tsunami Sri Lanka / Madhavi Malalgoda Ariyabandu, Ramona Miranda and Kusala Wettasinghe -- Adaptability to floods in North Bihar: gendered experiences / Eklavya Prasad with Vinay Kumar, Pradeep Poddar and Prem Verma -- Gender politics and disaster in rural Nepal / Sabrina Regmi -- Pakistan floods: reports from the field / Sana Saleem -- Rural women as architects of recovery and reconstruction: the Swayam Shikshan Prayog story / Prema Gopalan -- Gender-based violence and disasters: South Asia in comparative perspective / Brenda Phillips and Pamela Jenkins -- Gender, disasters and development: opportunities for South-South cooperation / Mihir Bhatt and Mehul Pandya with Zenaida Delica-Willison -- Exploring the meaning of securitisation for 'gender and disaster' / Nibedita S. Ray-Bennett -- Intersections and beyond / Swarna Rajagopalan.
Includes bibliographical references and index.
Keywords: Women disaster victims -- South Asia -- Social conditions; Women in disaster relief -- South Asia; Disasters -- South Asia; Emergency management -- South Asia; Public welfare -- South Asia; Women -- South Asia; Disasters; Emergency management; Public welfare; Women; Women in disaster relief; South Asia